Use of Herbal Medicines Among Breastfeeding Mothers in Tanzania: A Cross-Sectional Study - Millinga, Valeria Phelician; Im, Hyea Bin; Hwang, Jung Hye; Choi, Soo Jeung; Han, Dongwoon (Frontiers in Pharmacology, 2022)
Background: There are limited data on the use of herbal medicines (HM) among breastfeeding mothers, despite the fact that knowledge of the possible benefits or harms of HM use has a direct relationship with the health of infants, especially in resource-limited countries. The study aims to determine the prevalence and factors associated with HM use among breastfeeding mothers in Tanzania. Methods: The study followed a cross-sectional design using a structured survey questionnaire. Survey participants were recruited from the reproductive and child health clinic at Uhuru health center in Morogoro, Tanzania. The survey instrument comprised of 34 questions, including demographic information, the pattern of HM use during breastfeeding, and women’s perceptions of HM. Chi-square test and logistic regression were used for data analysis using SPSS ver. 24.0. Results: The majority of the respondents (53.8%) used HM during breastfeeding. The most commonly used HM was black pepper (Piper nigrum L.; 80.0%), followed by pumpkin seeds (Cucurbita pepo L.; 18.0%). About one-third (27.5%) of HM users discussed their use with their healthcare providers. In addition, higher education levels and low breastmilk supply were identified as potential predictors of HM use. Conclusion: The practice of HM use among breastfeeding mothers in Tanzania is popular to ease breastfeeding difficulties. However, the issue of the safety or effectiveness of HM is still an unknown agenda. This awakens the need to evaluate HM's safety, efficacy, and quality through pharmacological studies for scientific evidence. Lastly, a clinical guideline should be developed in healthcare settings to promote open dialogues between the healthcare providers and mothers to ensure the safe use of HM.